THE IMPLEMENTATION OF MERDEKA CURRICULUM IN ENGLISH TEACHING LEARNING - Sari, Arum Ambar; Fatmawati, Nor Laili (Yavana Bhasha : Journal of English Language Education, 2024)
In Indonesia, the phenomenon of curriculum change continues to experience various changes and improvements starting from the 1947 curriculum to the one that is being hotly discussed "Merdeka Curriculum". The objectives of this research were to describe the implementation of the Merdeka Curriculum in English teaching learning and to find the teacher's problems during the implementation of the Merdeka Curriculum in English teaching learning at the seventh grade of SMPIT Insan Mulia Surakarta in the academic year 2022/2023. In this study, researchers apply a qualitative descriptive method. Researchers collect data through observation, interview, and documentation. The data were obtained from two class observations from seventh grade and interview with English teacher. The results of the study show that the Merdeka Curriculum has been implemented in teaching English learning. The teacher makes Alur Tujuan Pembelajaran and Modul Ajar based on Merdeka Curriculum that is adapted to the characteristics of the educational unit. The teacher has also implemented a learning cycle and conducted an assessment based on the Merdeka Curriculum. Learning components in the form of objectives, materials, methods, media and evaluation have been fulfilled in English teaching learning. The problem faced by the teacher are the limited time to design differentiated learning based on the individual needs of students and the teacher cannot maintain student enthusiasm until the end of the lesson.